THE SOLUTION OF THE COSMOLOGICAL CONSTANT PROBLEM AND THE FORMATION OF THE SPACE-TIME CONTINUUM - Bukalov, A. V. (Одеські астрономічні публікації, 2016)
The application of the microscopic theory of superconductivity to describe the early Universe makes it possible to solve the problem of dark energy. In the cosmological models with superconductivity (CMS) this problem is solved in a natural way: dark energy is the result of pairing of primary fermions with the Planck mass, and its calculated density is equal to 6∙10-30 g/cm3 and is in good agreement with data of PLANK collaboration. At the same time the birth of space-time domains can also be described in the proposed model. Characteristic parameters of interaction of primary fermions determine the changes of the scale and values of different, but conjugate with each other, phase transitions – for the dark energy, the observed evolving Universe and other component of the condensate of primary fermions. y